Study on Consumers’ Preference and Price Premium for Organic Vegetables in Budhanilkantha Municipality Kathmandu Valley - Acharya, Arjun; Paudel, Sagar (JPAIR Multidisciplinary Research, 2022)
Paying regard to the increasing concern of consumers towards nutrients-loaded food products and agriculture sustainability, the main aim of this paper is to assess the consumers’ willingness to pay the price premium for organic vegetables and to know their perception of the organic vegetables in Budhanilkantha-8 municipality, Kathmandu. A total of 100 respondents were randomly surveyed using a questionnaire. The first part of the questionnaire included the demographic section, while in the second part, consumers were asked about their perception of organic vegetable consumption. The consumers’ survey revealed that 28% of the respondents were willing to pay a 0-10% price premium compared to inorganic vegetables. Similarly, 24% were willing to pay a 20-30% price premium. Some (22%) were willing to pay a 10-20% price premium, 9% liked to pay a 30-40% price premium, 1% liked to pay a 40-50% price premium, and 8% were willing to pay greater than 50% price premium, while 8% of surveyed consumers denied paying price premium even in case of product availability. The consumers’ willingness to pay was health properties, followed by freshness and taste. Few factors, such as low availability, low trust, lack of information, and high price, were considered barriers to purchasing organic vegetables. The survey also suggested that the consumption of organic vegetables is increasing; however, to stimulate further demand for its consumption, huge production and timely availability, credible certification, processing, and packaging are needed to be promoted.
Keywords: Business and Management; Organic vegetables; Price premium; Organic farming; Willingness to pay; consumer preference; agriculture sustainability; Nepal